Relationship marketing and its influence on purchase motivation in a hardware store in Cercado de Lima, 2025 - Cobos-Cruz, Milene Nataly; Fernández-Bedoya, Victor Hugo (LACCEI, 2025)
The objective of this research was to determine the influence of relationship marketing on purchase motivation (and its dimensions customer service, purchase interest, repurchase action and satisfied desire) in a hardware store in Cercado de Lima, 2025. Research with a quantitative approach, applied, with an explanatory and descriptive level, non-experimental and cross- sectional design. The finite population consisted of 92 customers of the company studied, whose sample amounted to 74 individuals. The technique applied was the virtual survey. The instrument to measure the first and second variable consisted of 8 items each, giving 16 items in total, and demographic data were also collected. Validity was obtained through the judgment of 4 experts (Aiken's V.= 1). Reliability was high for both variables (α = 0.709 and 0.805). Results such as demographic information, normality tests, measurement of variables and hypothesis testing were obtained. It was concluded that relationship marketing influences purchase motivation in a hardware store in Cercado de Lima, in the year 2025 (sig. = 0.000; R2 = 0.993).